Implementasi Media Sosial Dalam Pembelajaran Untuk Meningkatkan Kemampuan Berfikir Kritis Siswa Generasi Z - Tuti Nuriyati; Fatiha Fatiha; Lisma Wati; Ica Tamara Agustina (JURNAL MANAJEMEN PENDIDIKAN, 2026)
IMPLEMENTATION OF SOCIAL MEDIA IN LEARNING TO IMPROVE CRITICAL THINKING SKILLS OF GENERATION Z STUDENTS Abstract. This study aims to examine the implementation of social media as a learning medium to improve the critical thinking skills of Generation Z students. In the digital era, social media has become an integral part of students' daily lives, offering opportunities to support interactive and flexible learning processes. This research employs a qualitative approach by analyzing how social media platforms are utilized in the learning process and their impact on students' critical thinking abilities. The findings indicate that the integration of social media in education can enhance student engagement, encourage active participation, and foster critical thinking through discussion, collaboration, and information analysis. However, the effective use of social media requires proper guidance from educators to ensure that students can filter information wisely and use it responsibly. Therefore, social media can be an effective learning tool when used strategically and purposefully in educational contexts.